SOCIO-PSYCOLOGICAL ISSUES OF XENOPHOBIA, AIDS, TRADITION AND INNER –CITY STATUS IN PHASAWANE MPE‟S “WELCOME TO OUR HILLBROW” - Yasoda, S. Mazhali (International Journal of Psychosocial Rehabilitation, 2020)
Welcome to our Hillbrow‟ is a novel by South African novelist Phaswane Mpe which deals with issues of Xenophobia, AIDS, Tradition and Inner-City Status in the Hillbrow neighbourhood of Post-apartheid Johannesburg. It was first published in 2001.In the South African literary imagination, Hillbrow has come to represent everything frightening and promising about the new South Africa; it is at once a scene of drugs, crime and xenophobia toward immigrants. The seriousness with which Mpe handles the theme of Xenophobia in Welcome to our Hillbrow, seems to agree with the appeal by commentators such as Kolla pen (1999), for the dictionary meaning of Xenophobia should not to be confined to the fear and hatred of foreigners, but to includes its description as a violent practice that results in bodily harm and damage. This view may explain why Mpe puts xenophobia under a magnifying glass that elevates it above local society to national and international dimensions.